PENGARUH PENJAMINAN MUTU, KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA AKADEMIK DAN KOMITMEN KERJA TERHADAP KINERJA DOSEN DI KOTA JAMBI - Murniati, Erni (Jurnal Dinamika Pendidikan, 2014)
This research is aimed to determine the effect of quality assurance, transformational leadership, academic culture and work commitment toperformance.This quantitative research using a survey method and techniques of path analysis. The population was lectures of private higher Education in Jambi and 196 lectures were taken as samples and selected by using proportional sampling. The result of data analysis showed that: (1) quality assurance, transformational leadership, and work commitment effect positively to lecturesâ performance; (2) quality assurance, transformational leadership, and academic culture also effect positively to work commitment; (3) transformational leadership effect positively to academic culture. Therefore, the quality assurance, transformational leadership, academic culture, and work commitment in private higher education should be developed to improve lecturersâ performance.Keywords : Quality assurance, transformational leadership, academic culture, work commitment, and performance lecture